EFFECT OF ADMINISTRATION OF AQUEOUS EXTRACTS OF VERNONIA AMYGDALINA .DEL LEAVES TO GUINEA PIG DAMS ON MILK PRODUCTION AND CONTRACTION OF THE MAMMARY GLAND AND UTERUS. - Ijeh, I. I.; Igwe, K. K.; Ejike, Chukwunonso E. C. C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The effect of aqueous extracts of Vernonia amygdalina on litter-weight gain, milk production and uterine and mammary gland contraction amplitudes were investigated using guinea pigs as animal models. The animals were placed in four groups of three animals each with Group 1 as control and groups II-IV receiving 5 mg/kg, 10 mg/kg and 100 mg/kg V. amygdalina aquous extract respectively. Litters of animals in groups I, II, III and IV gained a mean weight (g) of 1.88 Â± 0.68, 3.11 Â± 0.10, 4.20 Â± 0.20 and 13.69 Â± 1.53 respectively, after five weeks. The differences in the mean weight-gain by the litters in groups II and IV, but not those in group II were significant (P< 0.05) when compared to the litters in the control group. All the dams had their highest milk production index (g) at week 2, with animals in groups I, II, III and IV having 11.00 Â± 1.00, 9.00 Â± 2.00, 11.33 Â± 5.69 and 14.33 Â± 1.53 respectively. The observed differences in milk production were not however significant (P< 0.05). Milk production dropped as the weeks progressed with the lowest for each group recorded at week 4 or 5. At concentrations of 5mg/ml, 10 mg/ml and 100 mg/ml, uterine contraction amplitudes (mm) were 1.22 Â± 0.03, 3.60 Â± 0.03 and 9.6 Â± 0.24 respectively. The uterine contraction amplitudes for 5 mg/ml and 10 mg/ml, but not 100 mg/ml V. amygdalina extracts were significantly (P< 0.05) lower than that recorded for equivalent concentrations of the standard drug – ergometrin. The mammary gland contraction amplitudes (mm) recorded for 5mg/ml, 10mg/ml and 100mg/ml V. amygdalina extract were 1.2 Â± 0.14, 2.70 Â± 0.36 and 6.15 Â± 0.13 respectively. The observed values were all significantly (P< 0.05) lower than those observed for the equivalent concentrations of ergometrin. Histopathological studies showed no marked toxicity of V. amygdalina extract on the cells of the major organs of the experimental rats, even at 100 mg/ml of the aqueous extracts of V. amygdalina.